QGIS python programming cookbook : over 140 recipes to help you turn QGIS from a desktop GIS tool into a powerful automated geospatial framework - Lawhead, Joel (Community experience distilled., 2015)
If you are a geospatial analyst who wants to learn more about automating everyday GIS tasks or a programmer who is responsible for building GIS applications, this book is for you. The short, reusable recipes make concepts easy to understand. You can build larger applications that are easy to maintain when they are put together.